Exploring the Therapeutic Potential of FSGTC for Osteoarthritis: A Comprehensive Study Combining Nested Case Analysis, Network Pharmacology, and Experimental Validation - He M; Liu J; Gao W; Sun Y; Chen X; Fang Y (Drug Design, Development and Therapy, 2025)
Mingyu He,1 Jian Liu,1 Wu Gao,2 Yanqiu Sun,1 Xiaolu Chen,1 Yanyan Fang1 1Department of Rheumatism Immunity, The First Affiliated Hospital, Anhui University of Chinese Medicine, Hefei, Anhui, 230031, People’s Republic of China; 2Sinopharm Group Jingfang (Anhui) Pharmaceutical Co., Ltd., Jingfang, Xuancheng, Anhui, 242000, People’s Republic of ChinaCorrespondence: Jian Liu, Department of Rheumatism Immunity, The First Affiliated Hospital, Anhui University of Chinese Medicine, 117 Meishan Road, Hefei, Anhui, 230031, People’s Republic of China, Tel +86 13955109537, Email liujianahzy@126.comObjective: This research aims to clarify the clinical efficacy and potential mechanisms of Fengshi Gutong capsule (FSGTC) in improving inflammatory response and hypercoagulability in osteoarthritis (OA) patients, and to evaluate the safety of FSGTC.Methods: A nested case-control study and association rule analysis were used to evaluate the effects of FSGTC on inflammation, coagulation, and liver and kidney function in OA patients. Screening key pathways for FSGTC treatment of OA through Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Subsequently, Hematoxylin-eosin staining (HE), Safranine O-Fast Green staining (S&O), and Immunohistochemistry (IHC) were used to evaluate the effects of FSGTC on cartilage injury, inflammatory cell infiltration, and protein expression in OA rats induced by monosodium iodoacetate (MIA). ELISA detects the expression of pro-inflammatory and procoagulant factors. Organ index and HE staining of organs to evaluate the safety of FSGTC treatment. Subsequently, further validate the above results in IL-1β - stimulated chondrocytes.Results: The clinical data analysis showed that FSGTC can significantly improve inflammation and coagulation indicators in OA patients. The KEGG pathway enrichment analysis results showed that PI3K/AKT is a key signaling pathway for FSGTC intervention in OA. Animal experiments have shown that FSGTC can alleviate cartilage damage and reduce inflammatory cell infiltration in OA rats, while having no effect on organs such as liver, heart, spleen, and kidney. The cell experiment results further confirmed that FSGTC increases chondrocyte viability and reduces the expression levels of COX2, PGE2 and PAI-1 by inhibiting the activation of the PI3K/AKT signaling pathway.Conclusion: FSGTC can alleviate inflammation and hypercoagulability in OA, and this therapeutic effect is attributed to its inhibition of PI3K/AKT pathway activation, thereby reducing the release of pro-inflammatory and procoagulant factors in OA patients, and the above drugs do not affect the liver and kidney function of patients. Keywords: osteoarthritis, fengshi gutong capsule, inflammatory response, hypercoagulable state, PI3K/AKT pathway